Strategi Peningkatan Kualitas Produk Lokal Ã¢â¬ÂTeh SepangÃ¢â¬ÂMenggunakan Metode Quality Function Deployment (Qfd) Di Kabupaten Sumbawa - Rahmawati, Sumarlin, Junaidi Efendi (Jurnal Biologi Tropis, 2017)
AbstractTeh SepangÃ¢â¬â¢ is a specialdrink of Sumbawanese people which included basic ingredient from Secang(Sepang)tree(CaesalpiniaSappan L). This research was aimed to know: attributes that becomecustomersÃ¢â¬â¢ priority to choose the local product that is tehsepangÃ¢â¬â¢.Identifiedthe variablesof techniqueproduction had direct influence in improvement the quality of local product tehsepangÃ¢â¬â¢. Analysed how far the quality product performance in customer needsÃ¢â¬â¢ and satisfaction. The method of this research wasdescriptive method, by using survey approach. This research was conducted in West Alas District, Sumbawa Regency. A technique of data collection was interview VOC (Voice of Customer) trough questioner. Technique of data sampling waspurposive sampling. The data in this research was analysed by using Quality Function Deployment (QFD).Based on the result of analysed Importance to Customer showed that there were 10 first important level from the customers of tehsepangÃ¢â¬â¢ that was; 1) The price appropriate with others attributes, 2) Man-power to produce tehsepangÃ¢â¬â¢, 3) The ingredients influence the taste, 4) ProductsÃ¢â¬â¢ Information, 5) Place of production, 6) ProductsÃ¢â¬â¢ Image, 7) The ingredients influence aromatic8) Appropriate technology,9) Compatibility ingredients of production, 10) ContentsÃ¢â¬â¢ protection (its mean that the pack can use to safe the tea). Whilefrom 10 variables of technique production there were three variables which most influencetowardthe product quality increase that was; mix all of the ingredients into tea pouch, packaging into available tea boxes, and sort out the materials. While the highest customersÃ¢â¬â¢satisfaction performance at three sub product attributes included herbal tea with customer satisfaction performance level in the amount of 4.17, sub attribute of the new local product customersÃ¢â¬â¢ satisfaction performance level in the amount of 4.57 and sub attribute of appropriate technology with customersÃ¢â¬â¢ satisfaction performance level in the amount of 3.87.ÃÂ Keywords: Quality Increase, TehSepangÃ¢â¬â¢, Importance to Customer, Quality Function Deployment